A study of Co‐Mn phosphate supported with graphene foam as promising electrode materials for future electrochemical capacitors. (11th October 2021) - Mirghni, Abdulmajid A.; Oyedotun, Kabir O.; Mahmoud, Badr A.; Fasakin, Oladepo; Tarimo, Delvina J.; Manyala, Ncholu
Summary: Mn and Co are known for their redox storage mechanism depending on the kinetics of their ions, which is required to boost capacity values of the material electrodes for energy storage applications. However, to the best of our knowledge, Co‐Mn phosphate material‐based electrochemical capacitors have been rarely investigated. In this work, CoMn(PO4 )2 synergized with graphene foam (GF) was synthesized following an easy, direct and low‐temperature hydrothermal method. The study investigated the synergy between Co, Mn and GF‐supported composite, with a strong P‐O covalent tie occurring at the surface of the material, leading to a high degree of polarization and very low relaxation time. The CoMn(PO4 )2 /GF material tested as a half‐cell could achieve a specific capacity of 58.15 mAh g −1 at 0.5 A g −1 . A CoMn(PO4 )2 /GF//activated carbon (AC) hybrid device was made up considering CoMn(PO4 )2 /GF and an AC material as positive and negative electrodes, respectively. The CoMn(PO4 )2 /GF//AC hybrid device achieved a specific capacity of 45.89 mAh g −1, specific energy of 51.53 Wh kg −1 and a corresponding specific power of 561.52 W kg −1 at 0.5 A g −1 . Furthermore, the device displayed a 95% capacity retention after 10 000 GCD cycles at 12 A g −1 and showed improved performance over its initial specific capacity after a voltage holding test for over 110 hours at 2 A g −1 . Abstract : Graphene foam (GF) was introduced into CoMn(PO4)2 as conductive support The CoMn(PO4)2/GF composite exhibited an improved electrochemical performances A hybrid device was assembled using the CoMn(PO4)2/GF and AC electrodes